2012
DOI: 10.1242/dev.069971
|View full text |Cite
|
Sign up to set email alerts
|

Trps1 activates a network of secreted Wnt inhibitors and transcription factors crucial to vibrissa follicle morphogenesis

Abstract: SUMMARYMutations in TRPS1 cause trichorhinophalangeal syndrome types I and III, which are characterized by sparse scalp hair in addition to craniofacial and skeletal abnormalities. Trps1 is a vertebrate transcription factor that contains nine zinc-finger domains, including a GATA-type zinc finger through which it binds DNA. Mice in which the GATA domain of Trps1 has been deleted (Trps1) have a reduced number of pelage follicles and lack vibrissae follicles postnatally. To identify the transcriptional targets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 59 publications
2
63
0
Order By: Relevance
“…This mechanism incorporates the findings from our in vitro studies into the well established molecular function of Trps1 as a transcriptional repressor (31)(32)(33)(34)(35). We cannot definitively rule out the possibility that in preodontoblasts Trps1 directly activates a subset of mineralization genes, as it has been demonstrated for Wnt pathway genes in hair follicle progenitor cells (36). However, thus far, there is no evidence that Trps1 can act as a transcriptional activator in cells other than hair follicle progenitors.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This mechanism incorporates the findings from our in vitro studies into the well established molecular function of Trps1 as a transcriptional repressor (31)(32)(33)(34)(35). We cannot definitively rule out the possibility that in preodontoblasts Trps1 directly activates a subset of mineralization genes, as it has been demonstrated for Wnt pathway genes in hair follicle progenitor cells (36). However, thus far, there is no evidence that Trps1 can act as a transcriptional activator in cells other than hair follicle progenitors.…”
Section: Discussionmentioning
confidence: 72%
“…Trps1 is a unique zinc finger protein that belongs to the GATA family of transcription factors (31). Although a majority of studies have demonstrated that Trps1 is a transcriptional repressor, recently it has been shown that during hair formation Trps1 can activate expression of Wnt pathway genes (32)(33)(34)(35)(36). Mutations of the TRPS1 gene in humans cause the craniofacial and skeletal dysplasia tricho-rhino-phalangeal syndrome (TRPS) and Ambras syndrome (37,38).…”
mentioning
confidence: 99%
“…In early hair follicle progenitors, TRPS1 is a transcriptional activator of genes that inhibit Wnt signaling (56), whereas it is a repressor of RUNX2, a gene important for osteoclast differentiation and maturation (57). Moreover, in odontoblast development, Trsp1 is an inhibitor of Dspp expression (58), whereas in chondrocytes, Trps1 controls proliferation and survival by repressing Stat3 expression (59).…”
Section: Discussionmentioning
confidence: 99%
“…Because TRPS1 represses transcription from GATA-containing binding sites (43,(56)(57)(58)(59), we searched for conserved GATA sites in the promoter regions of SERPINE1 and SERPINB2. We then designed oligonucleotides specific for these binding sites.…”
Section: Trps1 Regulates the Expression Of Multiple Genes In The Emtmentioning
confidence: 99%
“…Furthermore, it has recently been reported that Trps1 plays crucial roles in regulating the expression of several Wnt inhibitors and various transcription factors during vibrissa follicle morphogenesis in mice [75]. In humans, mutations in the TRPS1 gene are known to cause trichorhinophalangeal syndrome type I (TRPS I; MIM 190350) or type III (TRPS III; MIM 190351), both of which show an autosomal dominant inheritance trait, and are characterized by sparse hair and a number of craniofacial and skeletal abnormalities, such as peer-shaped nose and brachydactyly.…”
Section: Hereditary Hair Disorders Associated With Transcription Factorsmentioning
confidence: 99%